The impact of preoperative calcitonin screening on the prognosis of patients with medullary thyroid cancer: a retrospective multicenter cohort study - Hou, Yingtong; Yang, Yu; Chen, Gang; Long, Jianyan; He, Yufei; Xiong, Dandan; Pang, Yuyan; Li, Qi; Dong, Guojie; Qiao, Siqi; Chen, Wenke; Li, Xuyang; et al. (Endocrine, 2024)
Purpose There is still controversy in different guidelines regarding the necessity of routine preoperative calcitonin (Ctn) testing in medullary thyroid cancer (MTC). The level of preoperative Ctn may influence the extent of surgery. Methods This retrospective multicenter cohort study involved 149 MTC patients from 6 centers between 2013 to 2023. Clinical characteristics, surgical procedure and clinical outcomes were compared between Ctn-screened and Non-screened group. Kaplan–Meier method was used to estimate recurrence-free survival (RFS) and overall survival (OS). Results In total, 127 MTC patients with preoperative Ctn screening and 22 MTC patients without screening were analyzed. MTC patients with preoperative Ctn screening underwent more radical surgical procedures including total thyroidectomy and lymph node dissection, compared to those without screening (84.3% vs. 68.2% and 91.3% vs. 72.7%, respectively). The rate of recurrence and death were lower in the Ctn-screened group (16.1% vs. 36.4%, 0.8% vs. 18.2%, respectively). The survival curve showed a significantly better overall survival in Ctn-screened group than Non-screened group (HR:17.932, 95% CI 1.888–170.294, p -value = 0.001), while no significant difference was observed of RFS between two groups (HR:1.6, 95% CI 0.645–3.966, p -value = 0.307). Conclusion Preoperative Ctn screening can prompt surgeons choosing more radical initial surgical treatment for MTC patients, potentially leading to better long-term outcomes. Further evaluation of the cost-effectiveness of routine Ctn screening in thyroid nodule patients is warranted.